Encounters, Relations, Popular Culture and Representation - Gade, Solveig (Peripeti, 2023)
Interview with Bering by Gade. In this conversation, Gade draws a portrait of FIX&FOXY’s practices, and identifies some fundamental themes in contemporary theatre.